Aplikasi Metode Sequential Three-Stage Integer Goal Programming untuk Penjadwalan Kuliah - Nisrina Nafi’atul Huda; I Gusti Bagus Budi Dharma; Widya Wasityastuti (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2016)
Background: One of scheduling problems in educational sector currently was the course scheduling in college or well known as University Course Timetabling Problem (UCTP). The UCTP was comprehensive because of the policy difference among the university, faculties, and departments. The Faculty of Medicine Universitas Gadjah Mada, which organizes a block system has a different and more complex scheduling type than other faculties with non-block system. The porpose of this research was to build a mathematic model of block system UCTP in Faculty of Medicine Universitas Gadjah Mada to optimize the scheduling process time and results.Method: This research was conducted by dividing the scheduling problem into 4 sub – scheduling problems that are sequential, which are the scheduling of the 5 primary courses (lecture, panel discussion, practical sessions, tutorial, and skills laboratory), scheduling topics for each course, student’ group scheduling, and classroom scheduling. The problems are then modeled in the form of integer goal programming. Results: The block system scheduling model in Faculty of Medicine Universitas Gadjah Mada by considering topic and possibility of unavailability room using Sequential Three-Stage Integer Goal Programming has successfully developed and well verified.Conclusion: The model developed in this study is able to produce a schedule that meets all hard constraint in less than 24 hours. The result was more efficient compared to the previous trial-and-error method that consumed 30-45 days.